Long-term effect of intensive lifestyle intervention on cardiometabolic risk factors and microvascular complications in patients with diabetes in real-world clinical practice: a 10-year longitudinal study - Osama Hamdy; Shaheen Tomah; Mhd Wael Tasabehji; Hongxia Zhang; Marwa Al-Badri; Tareq Salah; Shilton Dhaver; Abdelrahman Khater (BMJ Open Diabetes Research & Care, 2023)
Introduction Intensive lifestyle intervention (ILI) has significantly reduced incidence of diabetes and improved many cardiovascular disease risk factors. We evaluated long-term effects of ILI on cardiometabolic risk factors, and microvascular and macrovascular complications among patients with diabetes in real-world clinical practice.Research design and methods We evaluated 129 patients with diabetes and obesity enrolled in a 12-week translational model of ILI. At 1 year, we divided participants into group A, who maintained <7% weight loss (n=61, 47.7%), and group B, who maintained ≥7% weight loss (n=67, 52.3%). We continued to follow them for 10 years.Results The total cohort lost an average of 10.8±4.6 kg (−9.7%) at 12 weeks and maintained an average weight loss of 7.7±10 kg (−6.9%) at 10 years. Group A maintained 4.3±9.5 kg (−4.3%) and group B maintained 10.8±9.3 kg (−9.3%) of weight loss at 10 years (p<0.001 between groups). In group A, A1c decreased from 7.5±1.3% to 6.7±0.9% at 12 weeks but rebounded to 7.7±1.4% at 1 year and 8.0±1.9% at 10 years. In group B, A1c decreased from 7.4±1.2% to 6.4±0.9% at 12 weeks then increased to 6.8±1.2% at 1 year and 7.3±1.5% at 10 years (p<0.05 between groups). Maintenance of ≥7% weight loss at 1 year was associated with a 68% lower risk of developing nephropathy for up to 10 years compared with maintenance of <7% weight loss (adjusted HR for group B: 0.32, 95% CI 0.11, 0.9, p=0.007).Conclusions Weight reduction in patients with diabetes can be maintained for up to 10 years in real-world clinical practice. Sustained weight loss is associated with significantly lower A1c at 10 years and improvement in lipid profile. Maintenance of ≥7% weight loss at 1 year is associated with decreased incidence of diabetic nephropathy at 10 years.